The Effect of Group Guidance With Ice Breaking in Improving Social Skills in Teenagers Addicted to Online Games - Al Ghifari Ahmadi Nadillah; Mirna Ari Mulyani; Sri Hertimi (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2026)
The rapid development of digital technology has had a significant impact on adolescents’ lives, one of which is the increasing addiction to online games, which affects social skills. Adolescents who experience online game addiction tend to interact less directly with others, have difficulties in communication, and exhibit low levels of empathy and social cooperation. This study aims to examine the effect of group guidance using ice-breaking techniques on improving social skills among adolescents addicted to online games. The study employed a quantitative, quasi-experimental design with a pre-test and post-test model, including an experimental and a control group. The research subjects were adolescents addicted to online games in Bungamas Village, Kikim Timur District, selected through purposive sampling. The results showed that in the group without ice-breaking treatment, there was no improvement in social skills between the pre-test and post-test. Meanwhile, in the group that received group guidance with ice-breaking techniques, there was an improvement in social skills with positive ranks (N = 4) and an average increase of 9.63. The Wilcoxon test results indicated an Asymp. Sig. (2-tailed) value of 0.013 (< 0.05), demonstrating a significant difference between pre-test and post-test scores. Therefore, it can be concluded that group guidance with ice-breaking techniques has a significant effect on improving social skills among adolescents addicted to online games.